The Effectiveness, Changes in Body Weight, and Menstrual Cycle Between 2 Rods and 1 Rod Contraceptive Implants after 12 Months of Insertion - Santoso, Budi; Susanto, Lunardhi; Tunjungseto, Arif; Widjayanti, Yhenti; Fernandus, Euvanggelia D.; Devianti Putri, Berliana (Current Women's Health Reviews, 2024)
Background: Implant as long-acting reversible contraception (LARC) is ideal for Indonesian women. Two-rod implant (2x75mg levonorgestrel) is the most common implant used in Indonesia. Another alternative method is a one-rod implant (1x150mg levonorgestrel). Objective: This study evaluated the effectiveness, changes in body weight (BW), and menstrual cycle between the one-rod and two-rod implant acceptors. Methods: This study was an RCT design with phase II clinical trials; 179 subjects were recruited. Subjects were met with inclusion and exclusion criteria and divided into one-rod and two-rod groups. The variables were evaluated within 12 months. Results: This study involved 70 subjects in the one-rod implant group and 66 subjects in the two-rod implant group. At 12 months, there were no differences between the effectiveness of the two types of contraception, and pregnancy was reported in 1.26% vs 1.31%. The concentration of levonorgestrel in the one-rod group was 0.31 ng/dL as the median (IQR: 0.33 ng/dL) and 0.34 ng/dL as the median (IQR: 0.33 ng/dL) in the two-rod group (p = 0.438). The BW in the two-rod group increased significantly in month six (p = 0.035) and twelve (p = 0.017) but not in the one-rod group. Menstrual cycle changes occurred in 51.4% of subjects and 57.6% of subjects in the one- and two-rod groups (p = 0.584), respectively. Conclusion: At 12 months, one-rod and two-rod implants had similar effectiveness and concentration of levonorgestrel. Significant weight gain happened in the two-rod group, and the weight gain increased in months six and twelve. Menstrual cycle changes have occurred in both.
Keywords: contraception